2021
DOI: 10.2217/rme-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human FGF-2 for the Treatment of Early-Stage Osteonecrosis of the Femoral Head: TRION, a Single-Arm, Multicenter, Phase II Trial

Abstract: Aim: This study aimed to evaluate the 2-year outcomes from a clinical trial of recombinant human FGF-2 (rhFGF-2) for osteonecrosis of the femoral head (ONFH). Patients & methods: Sixty-four patients with nontraumatic, precollapse and large ONFHs were percutaneously administered with 800 μg rhFGF-2 contained in gelatin hydrogel. Setting the end point of radiological collapse, we analyzed the joint preservation period of the historical control. Changes in two validated clinical scores, bone regeneration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Addressing this challenge, researchers have explored methods to establish sustained delivery systems for exosomes [48]. For instance, it has been demonstrated that incorporating FGF-2 into gelatin hydrogel enables long-term sustained release of FGF-2, thereby contributing to the improvement of ONFH [49,50]. Several studies have reported that encapsulating exosomes in hydrogels can maintain local concentration for long periods of time, thus providing therapeutic bene ts [47,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this challenge, researchers have explored methods to establish sustained delivery systems for exosomes [48]. For instance, it has been demonstrated that incorporating FGF-2 into gelatin hydrogel enables long-term sustained release of FGF-2, thereby contributing to the improvement of ONFH [49,50]. Several studies have reported that encapsulating exosomes in hydrogels can maintain local concentration for long periods of time, thus providing therapeutic bene ts [47,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant BMPs and fibroblast growth factor 2 (FGF-2) have been used for clinical application in combination with various carriers. [39][40][41][42][43] The therapeutic benefit of MSCs is known to be mostly attributable to factors they secrete. 44 In addition to growth factors and cytokines, cells communicate with neighbouring or distant cells via extracellular vesicles (EVs) including exosomes, which are EVs smaller than 150 nm in diameter.…”
Section: Delivery Of the Cellsmentioning
confidence: 99%
“…With this important development in hand, tissues with a high donor demand, such as bone and cardiac, have taken advantage of this revolutionary multidisciplinary area and dealt with donor scarcity [1]. In addition, some of the studies have reached clinical trials, being proof of the capacity of designed systems to regenerate tissue [5][6][7]. Nonetheless, although tissue engineering has opened up a new way of practicing medicine, there are some concerns in terms of cost-effectiveness, reproducibility or scalability that need to be addressed [8].…”
Section: Introductionmentioning
confidence: 99%